Lithium electrochemical cell comprising positive electrode based on lithium ferromanganese phosphate
By using low molecular weight monomers in electrochemical batteries for in-situ thermal polymerization, the gelled polymer electrolyte is solved, and the cycle life and Coulomb efficiency of the battery are improved.
Patent Information
- Application Number
- CN202380056477.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-11
- Publication Date
- 2025-03-28
AI Technical Summary
When the active material of the electrode is based on lithium ferromanganese phosphate, it is difficult to obtain good impregnation of the electrode pores by the gelled electrolyte, especially since the size of the electrode pores is smaller, with an average size less than 100 nm.
In situ thermal polymerization is performed using monomers containing at least two acrylate groups in an electrochemical cell to form a gelled polymer electrolyte, thereby improving the impregnation of the lithium ferromanganese phosphate positive electrode pores by the electrolyte.
This method improves the battery's lifetime and Coulomb efficiency during cycles, ensuring an increase in the ratio between the battery's discharge and the charged amount.
Smart Images

Figure CN119731799A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The technical field of the present invention is secondary electrochemical cells including a positive electrode (cathode) based on lithium manganese iron phosphate. BACKGROUND OF THE INVENTION
[0002] An electrochemical cell, also referred to hereinafter as a "battery", includes an electrochemical bundle composed of alternating positive and negative electrodes, with a separator impregnated with an electrolyte assembled. Each positive electrode and each negative electrode consists of a metal current collector that supports at least one active material on at least one of its faces, and usually a binder and a conductive material.
[0003] Rechargeable electrochemical cells of the lithium metal type are known in the prior art. Due to their high mass and volume energy density, they constitute a promising source of electrical energy. They include at least one positive electrode and at least one negative electrode, where the active material of the at least one positive electrode can be a lithium phosphate of at least one transition metal, and the active material of the at least one negative electrode is lithium or a lithium alloy.
[0004] The family of lithium phosphates of at least one transition metal consists of lithium manganese iron phosphate (abbreviated as LMFP) of the formula Li x Mn 1-y-z Fe y M z PO4, where 0.8 ≤ x ≤ 1.2; 0.5 ≤ 1 - y - z < 1; 0 < y ≤ 0.5 and 0 ≤ z ≤ 0.2. These phosphates contain manganese, iron, and one or more substitution elements represented by the symbol M. An interesting feature of these phosphates is that they have a working voltage of up to 4.5 V compared to Li + / Li.
[0005] Furthermore, it is known to use an electrolyte in a gelled form in an electrochemical cell. The gelled electrolyte can be obtained by dissolving a polymer in an organic solvent. Then the gelled electrolyte is brought into contact with the electrodes, and the electrodes are gradually impregnated by it. The gelled form has the following advantages: in the case of accidental opening of the battery container, it prevents the electrolyte from diffusing into the environment where the battery is placed. It also prevents the lithium dendrites that may form on the surface of the negative electrode from spreading to the positive electrode and generating a micro-short circuit that is harmful to the life of the battery. Compared with a liquid electrolyte, the gelled electrolyte improves the safety of the battery user.
[0006] However, it has been found that it is difficult to obtain good impregnation of the pores of the electrode by the gelled electrolyte when the active material of the electrode is based on lithium manganese iron phosphate. The pores of this type of electrode are very small. Its average size is actually less than 100 nm.
[0007] Therefore, when the active material is lithium manganese iron phosphate, methods are sought to improve the impregnation of the electrode pores with the gelled electrolyte.
[0008] US2005 / 0271939 discloses a secondary electrochemical cell comprising a negative carbon electrode and a positive electrode, wherein the positive electrode may be selected from LiNiO2, LiMn2O4, LiCoO2, LiCo 0.92 Sn 0.08 O2、LiCo 1-x Ni x Oxides of O2 and LiFePO4. The document discloses that the electrolyte may be a gelled electrolyte comprising a polymer obtained by copolymerization of a first monomer containing an acrylic acid or allyl group and a cyano group and a second monomer containing unsaturation in the α position. The document does not disclose a secondary electrochemical cell comprising a negative lithium electrode and a positive electrode being a lithium manganese iron phosphate. Summary of the invention
[0009] To this end, the present invention provides an electrochemical cell comprising:
[0010] - a negative electrode comprising an active material;
[0011] - a positive electrode comprising an active material comprising lithium manganese iron phosphate;
[0012] A gelled electrolyte comprising a matrix which is a polymer obtained by crosslinking monomers containing at least two acrylate groups, into which a liquid mixture comprising at least one solvent, at least one lithium salt and a thermal initiator for free-radical polymerization is incorporated.
[0013] According to one embodiment, the active material is selected from lithium metal and lithium alloys.
[0014] According to one embodiment, the polymer results from the crosslinking of propoxylated trimethylolpropane triacrylate (TPPTA).
[0015] According to one embodiment, the at least one lithium salt consists of a combination of lithium hexafluorophosphate (LiPF6) and lithium difluoro(oxalato)borate.
[0016] According to one embodiment, the at least one lithium salt consists of a ternary collaboration of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluoro(oxalato)borate.
[0017] According to one embodiment, the at least one solvent is a cyclic carbonate or a linear carbonate or a mixture thereof.
[0018] According to one embodiment, the at least one solvent of the electrolyte is selected from fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC) and mixtures thereof.
[0019] According to one embodiment, the free radical polymerization thermal initiator is azobisisobutyronitrile (AIBN).
[0020] According to one embodiment, the active material of the positive electrode comprises:
[0021] - 50% to 99% by mass of lithium manganese iron phosphate,
[0022] - 1% to 50% by mass of lithiated oxides of nickel, manganese and cobalt (NMC) and / or lithiated oxides of lithium, nickel, cobalt and aluminum (NCA) or mixtures thereof.
[0023] According to one embodiment, the lithium manganese iron phosphate has the formula: Li x Mn 1-y-z Fe y M z PO4, where 0.8 ≤ x ≤ 1.2; 0.5 ≤ 1 - y - z < 1; 0 < y ≤ 0.5 and 0 ≤ z ≤ 0.2, and
[0024] M is one or more chemical elements selected from B, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni, Cu, Zn, Y, Zr, Nb and Mo.
[0025] The present invention also relates to a method for in-situ thermal polymerization of a gelled polymer electrolyte in an electrochemical cell, the method comprising the following steps:
[0026] a) Providing an assembly comprising at least one positive electrode comprising an active material containing lithium manganese iron phosphate, at least one separator and at least one negative electrode comprising an active material;
[0027] b) Inserting the assembly into a container;
[0028] c) Preparing a liquid mixture comprising at least one solvent, a monomer containing at least two acrylate groups, at least one lithium salt and a free radical polymerization thermal initiator;
[0029] d) Impregnating the assembly with the liquid mixture;
[0030] e) Raising the temperature of the assembly to a temperature sufficient to cause crosslinking of the monomer containing at least two acrylate groups for a time in the range of 2 hours to 24 hours.
[0031] The present invention is based on the discovery that the impregnation of a positive electrode based on LMFP can be improved by carrying out an in-situ polymerization of a monomer containing at least two acrylate groups. The term "in-situ" means that the monomer is polymerized in such a way that a solution containing the monomer is in contact with an assembly comprising the at least one positive electrode, the at least one separator and the at least one negative electrode. Prior to the polymerization, the assembly is introduced into the container of the battery.
[0032] It has also been found that for monomers having at least two acrylate groups and having a low molecular weight, impregnation of the gelled electrolyte is improved.
[0033] Improved impregnation of the positive electrode leads to an increase in the life of the battery in cycles and an increase in the coulombic efficiency, that is to say an increase in the ratio between the amount of electricity discharged from the battery and the amount of electricity charged in the battery during the charging period before discharge.
[0034] According to one embodiment, step e) is carried out at a temperature ranging from 55°C to 80°C.
[0035] According to one embodiment, in step c), the mass percentage of monomers in the liquid mixture is 1% to 20% by mass of the mass of the combination formed by the at least one solvent, the at least one lithium salt and the thermal free-radical polymerization initiator.
[0036] According to one embodiment, in step c), the mass percentage of monomers in the liquid mixture is between 2% and 7% by mass of the mass of the combination formed by the at least one solvent, the at least one lithium salt and the thermal free-radical polymerization initiator. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings.
[0038] [ Figure 1 ] compared the double-layer capacitance of the positive electrode at 25 °C for different frequencies after formation of the cell when the electrolyte was gelled by cross-linking TPPTA and when the electrolyte was gelled by cross-linking PEGDA.
[0039] [ Figure 2 ] compared the resistance at 25° C. of a gelled electrolyte obtained by crosslinking TPPTA with that of a gelled electrolyte obtained by crosslinking PEGDA at different times after formation of the battery.
[0040] [ Figure 3 ] shows the variation of the capacity discharged by the battery of the example as a function of the number of cycles.
[0041] [ Figure 4 ] shows the change in the initial capacity retention percentage of the battery of the embodiment as a function of the number of cycles. DETAILED DESCRIPTION
[0042] Description of gelled polymer electrolytes
[0043] The polymer acts as a matrix in the gelled electrolyte. It is obtained by crosslinking a monomer containing at least two acrylate groups. Crosslinking refers to the formation of a polymer with a three-dimensional structure. The term "acrylate group" is included in the following methacrylate groups. The monomer usually contains two, three or four acrylate groups. In a preferred embodiment, crosslinking occurs only in the presence of a monomer containing at least two acrylate groups. The crosslinked polymer contains at least one acrylate group.
[0044] According to one embodiment, the reaction mixture does not comprise comonomers.
[0045] Examples of monomers having two acrylate groups are poly(ethylene glycol) diacrylate (PEGDA), poly(ethylene glycol) dimethacrylate (PEGDMA), poly(propylene glycol) diacrylate (PPGDA) and poly(propylene glycol) dimethacrylate (PPGDMA). Mention may be made of di(propylene glycol) diacrylate, 1H,1H,6H,6H-perfluoro-1,6-hexyl diacrylate, 1H,1H,5H,5H-perfluoropentane-1,5-diyl diacrylate and 2,2,3,3-tetrafluoro-1,4-butyl diacrylate. The number average molecular weight of poly(ethylene glycol) diacrylate (PEGDA) may range from 5000 g / mol to 10000 g / mol or from 6000 g / mol to 8000 g / mol. Its molecular weight may also range from 500 g / mol to 1000 g / mol, preferably from 600 g / mol to 800 g / mol. It has been observed that low molecular weight monomers facilitate the impregnation of the electrode pores with the gelled electrolyte.
[0046] Examples of monomers having three acrylate groups are trimethylolpropane triacrylate (TMPTA), pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate and propoxylated trimethylolpropane triacrylate (TPPTA).
[0047] An example of a monomer having four acrylate groups is pentaerythritol tetraacrylate (PETEA).
[0048] Among the above monomers, a preferred monomer is propoxylated trimethylolpropane triacrylate (TPPTA).
[0049] Crosslinking occurs by contacting the monomers with a free radical polymerization thermal initiator and activating the initiator by heat. The extent of crosslinking progress can be estimated by measuring the percentage of residual monomers in the reaction medium at different times during the reaction. Residual acrylate monomers are characterized by the presence of C=C double bonds in the vinyl group. This double bond can be detected by Fourier transform infrared spectroscopy (FT-IR). A person skilled in the art can use this technique to measure the amount of residual monomers. Crosslinking conditions are selected to minimize the amount of residual monomers. The presence of a small amount of residual monomers may have an adverse effect on the operation of the battery.
[0050] The electrolyte comprises one or more lithium salts, which may be selected from lithium perchlorate LiClO4, lithium hexafluorophosphate LiPF6, lithium tetrafluoroborate LiBF4, lithium hexafluoroarsenate LiAsF6, lithium hexafluoroantimonate LiSbF6, lithium trifluoromethanesulfonate LiCF3SO3, lithium bis(fluorosulfonyl)imide Li(FSO2)2N (LiFSI), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium tri(fluoromethanesulfonyl)methylate LiC (CF3SO2)3 (LiTFSM), lithium bis(pentafluoroethylsulfonyl)imide LiN(C2F5SO2)2 (LiBETI), lithium 4,5-dicyano-2-(trifluoromethyl)imidazolate (LiTDI), lithium bis(oxalato)borate (LiBOB), lithium difluoro(oxalato)borate (LiDFOB), lithium tris(pentafluoroethyl)trifluorophosphate LiPF3(CF2CF3)3 (LiFAP), lithium difluorophosphate LiPO2F2 and mixtures thereof.
[0051] A first preferred mixture of lithium salts consists of LiPF6 and LiDFOB, each in an amount of about 0.5 mol.L -1 The concentration used.
[0052] A second preferred mixture of lithium salts consists of LiPF6, LiFSI and / or LiTFSI and LiDFOB. Preferably, this second mixture consists of LiPF6, LiFSI and LiDFOB. This ternary mixture allows to reduce the adverse effects of the presence of residual acrylate monomers. In fact, these monomers form a passivation layer on the surface of the negative electrode during the formation of the battery, that is to say during the first charge / discharge cycle of the battery. This layer is resistive and contributes to increasing the internal resistance of the battery.
[0053] A monomer containing at least two acrylate groups, at least one lithium salt and a free radical polymerization thermal initiator are dissolved in at least one organic solvent. The organic solvent may be selected from saturated cyclic carbonates, unsaturated cyclic carbonates, linear carbonates, linear ethers, cyclic ethers and fluorinated derivatives thereof. Preferred saturated cyclic carbonates are propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC) and mixtures thereof. An example of fluorinated cyclic carbonates is monofluoroethylene carbonate (FEC). Vinylene carbonate may be used as an unsaturated cyclic carbonate. Preferred linear carbonates are dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dipropyl carbonate (DPC) and mixtures thereof. Preferred linear ethers include dimethyl ether (DME), diethyl ether (DEE) and mixtures thereof. Preferred cyclic ethers include lactones, such as gamma-butyrolactone.
[0054] In a preferred embodiment, the at least one solvent is selected from cyclic carbonates, linear carbonates and mixtures thereof.
[0055] In a preferred embodiment, the at least one solvent comprises fluoroethylene carbonate (FEC).
[0056] In one embodiment, the at least one solvent is a mixture of linear carbonate and fluoroethylene carbonate (FEC). The linear carbonate may be ethyl methyl carbonate (EMC).
[0057] In one embodiment, the at least one solvent is a mixture of fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC), and the salt mixture consists of LiPF6 and LiDFOB.
[0058] The free radical polymerization thermal initiator can be a compound containing one or more azo groups. Preferred initiators are those activated by temperatures in the range of 50°C to 100°C, 60°C to 90°C, or 70°C to 80°C. Moderate temperatures in the range of 55°C to 75°C are preferred. A free radical polymerization thermal initiator containing an azo group is azobisisobutyronitrile (AIBN).
[0059] Description of positive and negative electrodes:
[0060] The negative electrode contains an active material, preferably selected from lithium metal, lithium alloys. It can also be silicon, graphite, or a lithium-free active material. The term lithium-free active material refers to a sheet made of a metal other than lithium. The metal does not form an alloy with lithium ions. Before charging the battery, the surface of the metal sheet is free of lithium metal and is covered with a lithium layer during battery charging. The lithium alloy can be lithium alloyed with one or more elements selected from Mg, Al, Zn, Si, B, Ge, Ga, In, and Sn. More preferably, the only active material of the negative electrode is lithium metal or a lithium alloy. The active material can be attached to a current collector, which can be a copper strip.
[0061] At least one of the active materials of the positive electrode is lithium manganese iron phosphate having the following formula: Li x Mn 1-y-z Fe y M z PO4, where 0.8 ≤ x ≤ 1.2; 0.5 ≤ 1 - y - z < 1; 0 < y ≤ 0.5; 0 ≤ z ≤ 0.2, and M is selected from B, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni, Cu, Zn, Y, Zr, Nb, and Mo.
[0062] In one embodiment, 0.7 ≤ 1 - y - z ≤ 0.9 or 0.75 ≤ 1 - y - z ≤ 0.90.
[0063] In one embodiment, 0.15 ≤ y ≤ 0.25.
[0064] Typical formulas of lithium manganese iron phosphate are LiMn 0.8 Fe 0.2 PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 2 / 3 Fe 1 / 3 PO4, and LiMn 0.5 Fe 0.5 PO4.
[0065] In one embodiment, the lithium manganese iron phosphate is the only active material of the positive electrode.
[0066] In another embodiment, the lithium manganese iron phosphate is combined with a compound of the formula Li x M 1-y-z-w M’ y M” z M”’ wAt least one lithium oxide of at least one transition metal of O2(LMO2) is combined, wherein M, M', M", and M'' are selected from B, Mg, Al, Si, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, W and MO, provided that at least one of M, M', M", and M'' is selected from Mn, Co, Ni or Fe; M, M', M", and M'' are different from each other; and 0.8≤x≤1.4; 0≤y≤0.5; 0≤z≤0.5; 0≤w≤0.2 and x+y+z+w<2.1. One of M, M', M", and M'' can be Al with a stoichiometric index less than or equal to 0.1.
[0067] The lithium oxide of at least one transition metal may be a lithium nickel manganese cobalt oxide (NMC) or a lithium nickel cobalt aluminum oxide (NCA) compound, each of which has the formula:
[0068] Li w (Ni x Mn y Co z M t )O2(NMC), where 0.9≤w≤1.1; 0 <x;0<y;0<z;0≤t;
[0069] M is selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, Sr, Ce, Ta, Ga, Nd, Pr, La, and mixtures thereof,
[0070] Li w (Ni x Co y Al z M t )O2(NCA), where 0.9≤w≤1.1; 0 <x;0<y;0<z;0≤t;
[0071] M is selected from B, Mg, Si, Ca, Ti, V, Cr, Mn, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, Sr, Ce, Ga, Ta, Nd, Pr, La and mixtures thereof.
[0072] It may also be a mixture of NMC and NCA.
[0073] In one embodiment, the lithium oxide of at least one transition metal is NMC, wherein 0.6≤x.
[0074] In one embodiment, the lithium oxide of at least one transition metal is NMC, wherein 0.6≤x and 0.15≤y<0.40 or 0.20≤y≤0.30.
[0075] In one embodiment, the lithium oxide of at least one transition metal is NMC, wherein 0.6≤x and 0.10≤z<0.30 or 0.15≤z≤0.25.
[0076] When lithium manganese iron phosphate is mixed with at least one lithium oxide of a transition metal such as NMC, the lithium manganese iron phosphate may account for 50% to 99% by mass, or 55% to 75% by mass, or 60% to 80% by mass of the mixture. In another embodiment, the lithium manganese iron phosphate accounts for 1% to 50% by mass of the mixture.
[0077] A separator is provided between the positive electrode and the negative electrode. The separator may be composed of a layer of a material selected from polypropylene (PP), polyethylene (PE), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyester (e.g., polyethylene terephthalate (PET), polybutylene terephthalate (PBT)), cellulose, polyimide, and glass fiber. The separator may be composed of several layers of the above materials, which have the same properties or different properties. A layer (ceramic layer, such as aluminum oxide, or polyvinylidene fluoride (PVdF) or polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), or acrylate) may be coated on one or both sides of the layer. A preferred separator is composed of a polyethylene layer coated with an aluminum oxide layer on both sides.
[0078] Description of a method for preparing an in-situ gelled polymer electrolyte
[0079] In situ polymerization of monomers containing at least two acrylate groups allows to improve the impregnation of the LMFP pores with the electrolyte. Ex situ polymerization, that is to say carried out when the solution containing the monomers is not in contact with the at least one positive electrode, the at least one negative electrode and the at least one separator, does not allow to obtain such a good impregnation of the electrodes.
[0080] The electrochemical beam is prepared in a conventional manner by superimposing at least one positive electrode, at least one separator, and at least one negative electrode, each positive electrode being separated from the negative electrode by a separator.
[0081] This may be a planar or spiral arrangement of electrodes.
[0082] The assembly of the at least one positive electrode, the at least one separator and the at least one negative electrode is introduced into a container of the battery. The container may have a parallelepiped or cylindrical form. It may also be a flexible bag formed after welding the edges of two multilayer films, each of which comprises a metal layer sandwiched between two layers of plastic material.
[0083] Appropriate amounts of monomers, the at least one solvent, the at least one lithium salt and the thermal initiator are mixed to produce a liquid mixture. Typically, the mass percentage of the monomers ranges from 1% to 20% or 5% to 10% or 2% to 7% for the total mass of the at least one solvent, the at least one lithium salt and the free radical polymerization thermal initiator 100%. A low percentage of monomers allows a lower viscosity liquid mixture to be obtained, which improves the impregnation of the electrode.
[0084] The total amount of the thermal initiator used for free radical polymerization may be 0.1 to 3% by mass, desirably 1 to 1.5% by mass, relative to the mass of the monomer.
[0085] The assembly is immersed in the liquid mixture at room temperature. Preferably, a rest period, typically ranging from 12 hours to 24 hours, is observed to improve the penetration of the liquid mixture into the pores of the positive and negative electrodes.
[0086] The temperature is then raised to a value sufficient to activate the initiator and cause the monomers to crosslink. The temperature is typically set in the range of 50°C to 100°C, preferably 60°C to 70°C. When the free radical initiator is azobisisobutyronitrile (AIBN), the temperature may be set in the range of 60°C to 70°C. Depending on the amount of monomer and free radical initiator used, the heat is maintained for 2 hours to 24 hours, typically 5 hours to 15 hours. Using FT-IR technology allows checking whether the reaction mixture still contains compounds with C=C double bonds. Those skilled in the art will be able to know when to stop applying heat.
[0087] In the case of a rigid container in the form of a prismatic or cylindrical body, a cover including the current output terminals of the battery is provided on the opening of the container. The positive electrode terminal is electrically connected to the positive electrode and the negative electrode terminal is electrically connected to the negative electrode.
[0088] Cell closing can occur before or after cross-linking.
[0089] Example
[0090] Two pouch-sized electrochemical cells were manufactured. They differed in the composition of their gel electrolytes. The monomer in one cell was propoxylated trimethylolpropane triacrylate (TPPTA) with a number average molecular weight of 644 g / mol. The monomer in the second cell was polyethylene glycol diacrylate (PEGDA) with a number average molecular weight of 6000 g / mol. The two cells each comprised an assembly consisting of a positive electrode and a negative electrode separated by a separator. The assembly was housed in a flexible bag formed after fusing the edges of two multilayer films, each of which comprised a metallic aluminum layer sandwiched between two layers of plastic material. The positive electrode comprised a LiMnO2-containing electrolyte of 60 mass %. 0.8 Fe 0.2 PO4 and 40 mass% LiNi0.6 Mn 0.20 Co 0.20 The negative electrode consisted of a 60 μm lithium sheet attached to a current collector which was a copper tape. The separator consisted of a polyethylene layer covered with an aluminum oxide layer on both sides.
[0091] The gelled polymer electrolyte is obtained by in-situ crosslinking of monomers in a bag. For this purpose, a mixture of fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) is first prepared in a ratio of 20% by volume / 80% by volume. LiPF6 and LiDFOB are added to the mixture at a concentration of 0.5M each. A free radical polymerization thermal initiator is also added to the mixture in advance at a ratio of 0.1% by mass relative to the overall mass of FEC, EMC, LiPF6, LiDFOB and the monomer. The monomer is incorporated into the mixture at a ratio of 5% by mass of the monomer relative to the overall mass of the monomer, solvent, lithium hexafluorophosphate (LiPF6), lithium difluoro (oxalate) borate (LiDFOB) and the free radical polymerization thermal initiator. The liquid mixture is introduced into a bag including a positive electrode, a separator and a negative electrode. Crosslinking is initiated by exposing the bag to a temperature of 70°C for 7 hours.
[0092] The cells were subjected to formation consisting of two charge / discharge cycles at C / 10-D / 10 rates, followed by cycling at C / 5-D / 2 rates. During the test, opposite faces of the cells were subjected to a compressive force of 1 bar.
[0093] Complex impedance measurements show that the electrolyte resistance value of the battery whose electrolyte includes TPPTA stabilizes faster than the electrolyte resistance value of the battery whose electrolyte includes PEGDA.
[0094] Figure 1 The double layer capacitance of the positive electrode at 25°C was compared for different frequencies after battery formation when the electrolyte was gelled by cross-linking TPPTA and when the electrolyte was gelled by cross-linking PEGDA. The highest double layer capacitance was obtained for the battery in which the electrolyte was gelled by cross-linking TPPTA. This suggests that the electrolyte gelled by cross-linking TPPTA has better impregnation of the electrode. One reason may be the lower molecular weight of TPPTA compared to that of PEGDA, which would result in a lower viscosity of the liquid mixture before the monomers are cross-linked.
[0095] Figure 2The interfacial resistance between the lithium electrode and the TPPTA-based or PEGDA-based gel electrolyte at 25°C was compared. The interfacial resistance between the TPPTA-based gel electrolyte and lithium is lower than that between the PEGDA-based gel electrolyte and lithium. This result indicates that the resistance of the interface is smaller, and therefore when current passes through, a lower polarization associated with the interface will be obtained. In addition, the resistance value between the TPPTA-based gel electrolyte and lithium decreases faster over time, indicating that the latter is stable.
[0096] Both batteries were cycled. The variation of the discharge capacity of the battery as a function of the number of cycles is shown in Figure 3 middle. Figure 3 It is shown that the discharge capacity of the battery whose electrolyte is gelled with cross-linked PEGDA is slightly higher than that of the battery whose electrolyte is gelled with cross-linked TPPTA until the cycle number is about 12. After this cycle, the battery whose electrolyte is gelled with cross-linked TPPTA has the highest discharge capacity.
[0097] The change in the percentage of initial capacity retained as a function of the number of cycles is shown in Figure 4 For the battery whose electrolyte was gelled by cross-linked PEGDA, a rapid decrease in the retention of the initial capacity can be noticed. In addition, the Coulombic efficiency of the battery whose electrolyte was gelled by cross-linked TPPTA was 1% higher than that of the battery whose electrolyte was gelled by PEGDA. These results indicate that the use of low molecular weight monomers allows to improve the cycle life and Coulombic efficiency of the battery.
Claims
1. An electrochemical cell comprising: - a negative electrode comprising an active material; - a positive electrode comprising an active material comprising lithium manganese iron phosphate; A gel electrolyte comprising a matrix, said matrix being a polymer obtained by crosslinking monomers containing at least two acrylate groups, into which a liquid mixture comprising at least one solvent, at least one lithium salt and a thermal initiator for free-radical polymerization is incorporated.
2. The electrochemical cell of claim 1, wherein the active material is selected from lithium metal and lithium alloys.
3. The electrochemical cell according to claim 1 or 2, wherein the polymer results from the crosslinking of propoxylated trimethylolpropane triacrylate (TPPTA).
4. The electrochemical cell according to one of claims 1 to 3, wherein the at least one lithium salt consists of a combination of lithium hexafluorophosphate (LiPF6) and lithium difluoro(oxalato)borate.
5. The electrochemical cell according to one of claims 1 to 3, wherein the at least one lithium salt consists of a ternary collaboration of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium difluoro(oxalato)borate.
6. The electrochemical cell according to any preceding claim, wherein the at least one solvent is a cyclic carbonate or a linear carbonate or a mixture thereof.
7. The electrochemical cell of claim 6, wherein the at least one solvent of the electrolyte is selected from fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and mixtures thereof.
8. The electrochemical cell of any one of the preceding claims, wherein the free radical polymerization thermal initiator is azobisisobutyronitrile (AIBN).
9. The electrochemical cell according to claim 1 , wherein the active material of the positive electrode comprises: - 50% to 99% by mass of lithium manganese iron phosphate, 1 to 50% by mass of lithiated oxides of nickel, manganese and cobalt (NMC) and / or lithiated oxides of lithium, nickel, cobalt and aluminium (NCA) or mixtures thereof.
10. The electrochemical cell of any one of the preceding claims, wherein the lithium manganese iron phosphate has the formula: Li x Mn 1-y-z Fe y M z PO4, where 0.8≤x≤1.2; 0.5≤1-yz<1; 0 <y≤0.5;0≤z≤0.2, And M is one or more chemical elements selected from B, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni, Cu, Zn, Y, Zr, Nb and Mo.
11. A method for in-situ thermal polymerization of a gelled polymer electrolyte in an electrochemical cell, the method comprising the steps of: a) providing an assembly comprising: at least one positive electrode comprising an active material comprising lithium manganese iron phosphate, at least one separator and at least one negative electrode comprising the active material, b) inserting the assembly into a container, c) preparing a liquid mixture comprising at least one solvent, a monomer containing at least two acrylate groups, at least one lithium salt and a thermal initiator for free-radical polymerization, d) impregnating said assembly with said liquid mixture, e) raising the temperature of the assembly to a temperature sufficient to cause crosslinking of the monomer containing at least two acrylate groups for a time in the range of 2 hours to 24 hours.
12. The process according to claim 11, wherein step e) is performed at a temperature in the range of 55°C to 80°C.
13. The method according to claim 11, wherein in step c), the mass percentage of monomers in the liquid mixture is 1% to 20% by mass of the mass of the combination formed by the at least one solvent, the at least one lithium salt and the free-radical polymerization thermal initiator.
14. The method according to claim 13, wherein in step c), the mass percentage of monomers in the liquid mixture is 2 to 7 mass % of the mass of the combination formed by the at least one solvent, the at least one lithium salt and the free radical polymerization thermal initiator.
Citation Information
Patent Citations
Novel polymer electrolyte for electrochemical power sources
US20050271939A1